Enhanced hydroxide conductivity of imidazolium functionalized polysulfone anion exchange membrane by doping imidazolium surface-functionalized nanocomposites. Issue 63 (17th June 2016) - Li, Jianwei; Yan, Xiaoming; Zhang, Yuyan; Zhao, Baolin; He, Gaohong
Abstract : A new method was proposed to prepare a membrane with regional aggregation of functional groups by incorporating nanocomposites surface-functionalized with a large number of functional groups. Abstract : A new method was proposed to prepare a membrane with regional aggregation of functional groups by incorporating nanocomposites surface-functionalized with a large number of functional groups. Imidazolium surface-functionalized SiO2 (SiO2 -Im) nanocomposites were synthesized by the reaction of 1, 2-dimethylimidazole, γ-chloropropyl triethoxysilane and SiO2 nanocomposites. The obtained SiO2 -Im nanocomposites were incorporated into imidazolium functionalized polysulfone (PSf-Im) to fabricate composite alkaline anion exchange membranes. The uniform dispersion of nanocomposites in the membrane was demonstrated by SEM. With increasing mass ratio of SiO2 -Im from 0% to 20%, hydroxide conductivity of composite membrane dramatically increases at first and then decreases. The composite membrane with 12 wt% of SiO2 -Im shows the highest conductivity, e.g., the hydroxide conductivity of the composite membrane based on PSf-Im with functionalization degree of 76% reaches 32 mS cm −1 (at 20 °C) that is 68% higher than the membrane's without doping SiO2 -Im (19 mS cm −1 ). In addition, adding SiO2 -Im has a slight effect on water uptake and swelling ratio of composite membrane. It indicates that doping surface-functionalized nanocomposites is a simple and effective method to enhance the hydroxide conductivity without increasing swelling.